Efeito de bloqueadores de transportadores ABC e derivados cumarínicos sobre gametas e embriões de ouriços-do-mar Echinometra lucunter (Echinodermata:echinoidea) expostos à radiação ultravioleta - Leite, Jocelmo Cassio de Araujo (2015)
Ultraviolet radiation (UV) environmental levels have increased in last years and high values are expected until half of this century. Gametes and embryos of marine organisms, whose embryonic development occurs externally, are particularly sensitive to UVA and UVB radiations. The first line of cellular defense against chemical or physical stress is the activity of ABC transporters. The aim of present work was investigate the involvement of ABC transporters on UVA or UVB effects on gametes or embryos of the sea urchin Echinometra lucunter, and investigate the photoactivity and the ABC transporter blocker activity of coumarin and 3-hydroxycoumarin in gametes and embryos of E. lucunter. Gametes or embryos were exposed to UVA (3.6 – 14.4 kJ m-2) or UVB (0.112 – 14.4 kJ m-2), and the embryonic development was monitored by optical microscopy at different developmental stages in the presence or absence of the ABC-transporter blockers reversin205 (ABCB1 blocker) ou MK571 (ABCC1 blocker). E. lucunter eggs, spermatozoa and embryos were resistant to UVA exposure. Resistance to the harmful effects of UVB was strongly associated to ABC transporter activity (embryos > eggs > spermatozoa). ABCB1 or ABCC1 blockage promoted injurious effects on spermatozoa exposed to UVA. ABCC1 transporter blockage increased UVB-dependent damage in eggs while ABCB1 transporter inhibition increased harmful effects of UVB in embryonic cells. ABC transporters blockers also induced abnormalities in larval development derived from spermatozoa or eggs irradiated to UVB. However, ABC transporter activity was not affected by UVB exposure. Additionally, we demonstrate the photoprotective activity of coumarin and 3-hidroxycoumarin against the deleterious effects of UVB on E. lucunter gametes and embryonic cells, and the ABC transporter blocker activity of the 3-hydroxycoumarin. In conclusion, the present study is the first report of the protective role of ABC transporters against UVA and UVB injurious effects in sea urchins gametes and embryonic cells. Furthermore, our results inserts new alternative for the treatment of various diseases related to UVB excessive exposure and also provides alternatives for clinical reversal of multidrug resistance phenotype.